The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1105/tpc.15.00492
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Resequencing Reveals Extensive Natural Variation in the Model Green Alga Chlamydomonas reinhardtii

Abstract: We performed whole-genome resequencing of 12 field isolates and eight commonly studied laboratory strains of the model organism Chlamydomonas reinhardtii to characterize genomic diversity and provide a resource for studies of natural variation. Our data support previous observations that Chlamydomonas is among the most diverse eukaryotic species. Nucleotide diversity is ;3% and is geographically structured in North America with some evidence of admixture among sampling locales. Examination of predicted loss-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
114
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 81 publications
10
114
2
Order By: Relevance
“…However, it is interesting to note that the rate of variants within these blocks, 2.0%, was comparable to the 2.4% rate of variation that we observed in CC-2290, as well as the 2.83% average variant rate for wild isolates of Chlamydomonas as reported by Flowers et al (2015). (A) Identification of variants.…”
Section: The Genomes Of the Chlamydomonas Standard Laboratory Strainssupporting
confidence: 85%
See 1 more Smart Citation
“…However, it is interesting to note that the rate of variants within these blocks, 2.0%, was comparable to the 2.4% rate of variation that we observed in CC-2290, as well as the 2.83% average variant rate for wild isolates of Chlamydomonas as reported by Flowers et al (2015). (A) Identification of variants.…”
Section: The Genomes Of the Chlamydomonas Standard Laboratory Strainssupporting
confidence: 85%
“…In work cosubmitted with this article, Flowers et al (2015) also observed ways in which mutations present in the sequenced strains of Chlamydomonas were biased toward those that are less deleterious to gene expression. For example, they observed that 28% of genes with premature stop codons encode proteins that are truncated by 5% or less.…”
Section: Effects Of Haplotype 2 On Genesmentioning
confidence: 92%
“…Therefore, during the RNA-seq mapping, we allowed three mismatches after considering average synonymous polymorphism among the field isolates (nucleotide diversity at synonymous sites, dS = 0.0317, Flowers et al, 2015). As a result, mapping rates range between 82.1% and 98.2% of the total reads (Supplemental Table S2).…”
Section: Experimental Design For Identifying Ez-specific Genesmentioning
confidence: 99%
“…In a related study of genomic diversity in Chlamydomonas, Flowers et al (2015) used whole-genome resequencing to analyze genetic diversity in 12 field isolates from Phenotypic variation of Chlamydomonas laboratory strains in response to iron concentration (top panel). Geographic clustering of field strains is shown in the bottom panel.…”
mentioning
confidence: 99%
“…Geographic clustering of field strains is shown in the bottom panel. (Reprinted from Gallaher et al [2015], Supplemental Figure 1A, and Flowers et al [2015], Figure 2A. ) www.plantcell.org/cgi/doi/10.1105/tpc.15.00778…”
mentioning
confidence: 99%